Prophylaxis and treatment of malaria in HIV-infected populations. (September 2008) - Achan, Jane; Gasasira, Anne F; Aweeka, Fran; Havlir, Diane; Rosenthal, Philip J; Kamya, Moses R
Malaria and HIV infection are among the most important infectious diseases worldwide. Management of each infection may affect the other. Insecticide-impregnated bed nets and prophylaxis with trimethoprim––sulfamethoxazole have greatly reduced the incidence of malaria in HIV-infected individuals. Artemisinin-based combination therapies are highly effective malaria treatments, although recrudescence and new infections after therapy occur more commonly in HIV-infected than uninfected patients. These immune dysregulatory effects of HIV on malaria treatment outcomes may, however, be less important in children. Interactions of malaria and HIV therapies may lead to unanticipated risks of adverse events. Antiretroviral protease inhibitors demonstrate in vitro antimalarial activity. Further study is needed on the impacts of different therapies on the prevention of malaria, selection of resistance and toxicity.